Clinicopathological Characteristics of Gastric Hepatoid Adenocarcinoma - Jung Bin Yoon; Gwang Ha Kim; Do Youn Park; Young Geum Kim; Sung Ik Pyeon; Bong Eun Lee; Geun Am Song (Yong Chan Lee, 2017)
Background/Aims: Gastric hepatoid adenocarcinoma (GHA), a rare type of primary gastric cancer, is characterized by a histology resembling hepatocellular carcinoma. Previous case studies reported that patients with GHA have a poor prognosis due to early lymph node or liver metastasis, but information concerning GHA is still limited. Therefore, we aimed to evaluate the clinicopathological features of GHA. Materials and Methods: We reviewed the medical records of 9 patients who were diagnosed as having GHA between January 2011 and December 2016. The clinicopathological characteristics of these patients were retrospectively analyzed. Results: The median age of the patients at diagnosis was 68.9 years. Seven of the 9 patients were male. Serum AFP levels were elevated in 3 of 4 patients. All the tumors were ＞4 cm (range, 4∼12 cm), and 7 tumors were located at the lower third of the stomach. Five tumors were classified as Borrmann's type 3, with a purple, berry-like surface. Of the 6 patients without distant metastasis, 5 received curative-intent surgery and 3 received adjuvant chemotherapy. Three patients with distant metastasis received either palliative operation and/or chemotherapy. Their median survival time was 11.8 months (range, 1∼36 months). Two patients with elevated serum CEA levels had poor outcomes. Conclusions: GHA is a rare subtype of gastric cancer that is prone to liver metastasis. All GHAs are advanced gastric cancer with a purple, berry-like surface at diagnosis. Although the prognosis of advanced-stage GHA is poor, active multimodality treatment might provide some benefit.